Edukasi Bentuk Kampanye Sosial Menggunakan Media Sosial Di SMA Negeri 8 Kota Bengkulu - Irawan, Tinton; Amelia, Putri Ricki; Afriandi, Afriandi; Jusiati, Arini; Octaviani, Vethy; Maryaningsih, Maryaningsih; Narti, Sri (Universitas Dehasen Bengkulu, 2025)
Social media-based campaings have become one of the effective strategies to raise students awareness of social issues, such as mental health, digital literacy, and environmental concerns. This study aims to educate students of SMA Negeri 8 Kota Bengkulu on utilizing social media positively through educational programs and social campaings conducted as part og the Kuliah Kerja Nyata Tematik (KKNT) program by Universitas Dehasen Bengkulu. The methods employed in this research indclude an initial survey to understand students needs, training sessions to enhance an initial survey to understand students needs, training sessions to enhance their skills, production of educational content, publications through social media platforms, and evalution to measrue the effectiveness of the activities. The results indicate an improvementin students understanding of the concept of digital social campaigns and their creativity in producing educational content. Additionally, the students showed enthusiasm in disseminating positive messages via social media. Based on these findings, this study recommends strengthening digital literacy programs in schools to support the sustainability of social media-based campaigns. Thus, students can transform from passive consumers to active producers of content that positively contributes to their social environment.